Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1111/j.1365-2958.1992.tb01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Conjugative transfer functions of broad‐host‐range plasmid RK2 are coregulated with vegetative replication

Abstract: The kilB locus (which is unclonable in the absence of korB) of broad-host-range plasmid RK2 (60 kb) lies between the trfA operon (co-ordinates 16.4 to 18.2 kb), which encodes a protein essential for vegetative replication, and the Tra2 block of conjugative transfer genes (co-ordinates 20.0 to 27.0 kb). Promoter probe studies indicated that kilB is transcribed clockwise from a region containing closely spaced divergent promoters, one of which is the trfA promoter. The repression of both promoters by korB sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 84 publications
1
71
2
1
Order By: Relevance
“…The reading frames for traF and traG contain overlapping start/stop codons (23a, 56 (24,40). Functions mapping within Tra2 include phage sensitivity, entry exclusion, and the locus kilB, also designated trbB (28,35). The kilB gene, which has homology with virBIl of A. tumefaciens (35), has been shown by mutation and complementation analysis to be required for transfer (27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reading frames for traF and traG contain overlapping start/stop codons (23a, 56 (24,40). Functions mapping within Tra2 include phage sensitivity, entry exclusion, and the locus kilB, also designated trbB (28,35). The kilB gene, which has homology with virBIl of A. tumefaciens (35), has been shown by mutation and complementation analysis to be required for transfer (27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Functions mapping within Tra2 include phage sensitivity, entry exclusion, and the locus kilB, also designated trbB (28,35). The kilB gene, which has homology with virBIl of A. tumefaciens (35), has been shown by mutation and complementation analysis to be required for transfer (27) (Fig. 1) (25, 31) t' appear to adsorb to pili (7,8), it has not been demonstrated that these pili are sex pili or that all phage resistance is due to loss of these pili.…”
Section: Resultsmentioning
confidence: 99%
“…VirB11 belongs to the family of PulE-like NTPases found in type II, type IV and tad-like secretion systems (Motallebi-Veshareh et al, 1992;Planet et al, 2001;Whitchurch et al, 1991). Along with VirB4 and the CP (VirD4), VirB11 is thought to energize the type IV secretion machinery either for complex assembly, pilus production and/or substrate secretion.…”
Section: Virb11: a Ring-shaped Cytoplasmic Ntpase Fuelling The Secretmentioning
confidence: 99%
“…The structure of H. pylori Cag525 protein [138], a member of the VirB11/PulE family of ATPases [144] involved in the type-IV secretion system of the latter pathogen, reveals a six-clawed grapple shape mounted on a hexameric ring and it is proposed to be membrane-associated. It has been shown to function as dynamic hexameric assemblies with nucleotide-dependent conformational changes regulating substrate export or T4SS assembly [145].…”
Section: Working Hypothesis For Conjugative T4cpsmentioning
confidence: 99%